Menggabungkan Edukasi dan Kreativitas Melalui Kegiatan Belaria dengan Lomba Mewarnai di Desa Sumokembangsri - Nur Sa’adatut Daraini; Nurul Taqwa; Raudotul Jannah; Masfufah Masfufah; Nelud Darajaatul Aliyah; Mirza Elmy Safira; Eli Masnawati; Yayu Sriwahyuni Hamzah; Utami Puji Lestari (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The Belaria activity, in the form of a coloring competition using the Participatory Action Research (PAR) empowerment method, aims to improve the creative skills and understanding of participants through a collaborative and participatory approach. The PAR method is applied to actively involve participants in every stage of the activity, from planning to evaluation, so that they can contribute and reflect on the coloring process. In this coloring competition, participants are invited to color pictures with certain relevant themes, such as plants and animals, with a focus on the application of basic coloring techniques. Evaluation is carried out through direct observation and participatory feedback, to assess the effectiveness of the method in developing participants' skills and measuring its impact on their understanding of the coloring process. The results of the activity show that this activity has succeeded in empowering participants, increasing their involvement in the creative process, and utilizing free time. This competition not only provides a forum for creative expression but also strengthens participants' ability to collaborate and reflect on learning experiences